Design of high power amplifier based on wilkinson power combiner for wireless communications - Tran Van Hoi; Ngo Thi Lanh (Institute of Advanced Engineering and Science, 2021)
Thisarticlepresentsthedesign and fabrication ofa high power amplifierbased onwilkinson power combiner. A 45W basic amplifier module isdesigned usinglaterally-diffused metal-oxide semiconductor (LDMOS) fieldeffect transistor (FET) PTFA260451E transistor. Wilkinson power combineris used to combine two input powers toproduce 90W of power. Theproposed power amplifier is researched, designed and optimized usingadvanced design system(ADS) software.Experimental results show that thegain is 11.5 dB greater than at 2.45-3.0GHz frequency band and achieving maximum power gain of 13.5dB at 2.65GHz centre frequency; output power increased to 49.3dBm; Power added efficiency of 62.1% and good impedances matching: input reflection coefficient (S11)<-10dB, output reflection coefficient (S22)<-15dB. The designed amplifier can be used for4G, 5G mobile communications andS-band satellite communication.